Menumbuhkan Kesadaran Kebersihan dan Sanitasi melalui Pendidikan Agama Islam - Fajar Sidik; Mustabsyiroh Mustabsyiroh; Rini Rini (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Awareness of cleanliness and sanitation is a crucial aspect in developing healthy lifestyles in students. From the perspective of Islamic Religious Education (PAI), cleanliness values ​​are understood not only as physical practices but also as an integral part of self-purification, spiritual strengthening, and the realization of faith in daily life. This literature review aims to examine how Islamic religious education plays a role in fostering awareness of cleanliness and sanitation in educational settings. This research utilizes scientific sources such as reputable journals, academic books, and relevant research reports. Previous study findings indicate that Islamic teachings on purification, cleanliness etiquette, and environmental responsibility are strongly relevant in improving students' hygiene behavior. The PAI approach, through integrative learning, teacher role models, religious practices, and strengthening school culture, has been shown to foster positive attitudes toward personal and environmental hygiene. Furthermore, the integration of cleanliness values ​​into the PAI curriculum encourages students to understand the spiritual significance of maintaining sanitation, rather than simply carrying out technical activities. This study concludes that PAI has significant potential in increasing awareness of cleanliness and sanitation when implemented with a holistic, contextual, and role-model-based approach. This research's recommendations include developing a model for Islamic Religious Education (PAI) learning based on clean and healthy living behaviors (PHBS) and increasing collaboration between Islamic Religious Education (PAI) teachers and schools to build a sustainable culture of cleanliness.